Analisis Strategi Pemasaran dan Bauran Pemasaran di Era Digital dalam menghadapi Persaingan di UMKM Rajawali Persada Coffee - Karina Komariah Hidayat; Elizabeth Olivia Ina Barek; Muhamad Ardi Nupi Hasyim (STIE Bangkinang Publishing, 2023)
Technological developments and increasingly high business competition have forced Micro, Small and Medum Enterprises (MSMEs) to have a good marketing strategy to remain competitive with their competitors. This research was conducted to determine the marketing strategy and marketing mix in the digital era in facing competition from MSMEs. The research method in this study used a qualitative approach through interviews, observation, documentation and structured questionnaires with MSME owners. The explanation from the research shows that coffee is not just a drink to quench thirst, but also to find out its origins. Drinking coffee is a tradition for the people of Indonesia, it's just that coffee used to be consumed by the elderly, but now it's different from now where almost all people like to drink coffee. In running this MSME business using a marketing mix such as product strategy, price strategy, place strategy, and promotion strategy. When viewed in terms of the digital era marketing strategy, MSMEs will step into the digitalization era and develop marketing and innovation. The results of the study show that the things that must be considered in online marketing are competitive prices, attractive packaging and easy access. In terms of implementing this technology, MSMEs use promotion and social media as a developing advertising method, communicating with consumers, collecting feedback and suggestions about coffee products.